Hispanismo e latinismo no debate intelectual ibero-americano - Beired, José Luis Bendicho [UNESP] (Pós-Graduação em História, Faculdade de Filosofia e Ciências Humanas, Universidade Federal de Minas Gerais., 2014)
This work aims to address two different streams of opinions in the ibero-american scenario, the hispanism and the latinism, both committed to building transatlantic cultural communities in the 19th and 20th Centuries. Some intellectuals had a privileged position in the formulation of ideas, programs and initiatives in order to strengthen the ties between the European and American worlds, just as they were the protagonists of controversies that crossed the national frontiers. The criticism to the United States established the background for the fight that the Spanish and French waged to claim the leadership on the countries located south of the Rio Bravo. We will focus on some situations and characters that inspired such opinions in order to understand their positions and antagonisms.

Neste trabalho serão abordadas duas correntes de opinião do cenário ibero-americano, o hispanismo e o latinismo, ambas empenhadas na construção de comunidades culturais transatlânticas nos séculos XIX e XX. Os intelectuais tiveram lugar privilegiado na formulação de ideias, programas e iniciativas com a finalidade de estreitar laços entre o mundo europeu e o americano, assim como foram protagonistas de polêmicas que atravessaram as fronteiras nacionais. A crítica aos Estados Unidos constituiu o pano de fundo da luta que espanhóis e franceses travaram para reivindicar a liderança sobre os países ao sul do Rio Bravo. Enfocaremos algumas conjunturas e personagens que animaram tais correntes de modo a compreender suas posições e antagonismos.
Hispanism and latinism in the Ibero-American intellectual debate
Keywords: hispanismo; latinismo; ibero-americanismo; hispanism; latinism; Ibero-Americanism